Porous N- and S-doped carbon–carbon composite electrodes by soft-templating for redox flow batteries - Schnucklake, Maike (Beilstein J Nanotechnol, 2019)
Highly porous carbon–carbon composite electrodes for the implementation in redox flow battery systems have been synthesized by a novel soft-templating approach. A PAN-based carbon felt was embedded into a solution containing a phenolic resin, a nitrogen source (pyrrole-2-carboxaldehyde) and a sulfur source (2-thiophenecarboxaldehyde), as well as a triblock copolymer (Pluronic(®) F-127) acting as the structure-directing agent. By this strategy, highly porous carbon phase co-doped with nitrogen and sulfur was obtained inside the macroporous carbon felt. For the investigation of electrode structure and porosity X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and nitrogen sorption (BET) were used. The electrochemical performance of the carbon felts was evaluated by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The N- and S-doped carbon electrodes show promising activity for the positive side reaction and could be seen as a significant advance in the design of carbon felt electrodes for use in redox flow batteries.